Application of numerical techniques to the recognition of structural controls on porphyry Cu mineralization: a case study of Dehaj area, Central Iran. Issue 3 (3rd May 2020) - Habibkhah, Narges; Hassani, Hossein; Maghsoudi, Abbas; Honarmand, Mehdi
ABSTRACT: This paper endeavours to evaluate the structural controls of porphyry copper mineralization in Dehaj area, Central Iran, using numerical techniques, an aim for which the various data types including the location of mineral deposits, stream sediment geochemical data and faults were employed. Initially, classical statistics and the concentration-area (C-A) fractal methods were applied to identify mineralization-related geochemical anomalies, revealing the superiority of fractal technique over the traditional methods employed. In addition, a rose diagram portraying the distribution of mineral locations was compared to the distribution and trends of faults using fractal and fry analyses, showing that the spatial pattern of porphyry copper deposits is closely linked to NW- and E-trending faults. In other words, the aforementioned structural trends were plausibly the chief geographical directions controlling the mineralization. The results of this study suggest that NW- and E-trending faults have plausibly operated as corridors for the transportation of ore-bearing fluids.